2017
DOI: 10.1111/jdv.14278
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide differential expression profiling of long non‐coding RNAs in androgenetic alopecia in a Chinese male population

Abstract: To our knowledge, this is the first study to investigate AGA-associated lncRNAs. lncRNA profiles are altered in AGA, and these lncRNAs and their target genes may serve as novel candidates for preventing and treating AGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[36][37][38][39] A Chinese study has suggested that AGA-associated long noncoding RNAs and their target genes may serve as promising therapeutic targets for preventing and treating AGA. 40 Further studies will be needed to confirm the efficacy and safety of these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39] A Chinese study has suggested that AGA-associated long noncoding RNAs and their target genes may serve as promising therapeutic targets for preventing and treating AGA. 40 Further studies will be needed to confirm the efficacy and safety of these treatments.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that inflammatory immune cells, such as CD4 + and CD8 + T cells, lead to dystrophic hair follicle cycling with premature entry into the telogen phase in alopecia areata-affected mice or human models ( Strazzulla et al, 2018 ). There is no existing evidence to show that inhibiting inflammation can treat androgenic alopecia, although more inflammatory molecules were found in skin regions affected by androgenic alopecia areas than the unaffected areas ( Bao et al, 2017 ). However, previous WIHN studies have shown that inflammation-related factors are capable of promoting de novo hair follicle growth ( Gay et al, 2013 ; Nelson et al, 2015 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, for the biology of hair follicle, specific lncRNAs, such as ANCR, TINCR, HOTAIR, SPRY4-IT1 have been identified to be involved in the regulation of the HF cycle (Wan and Wang, 2014). Bao et al (2017) reported a total of 2143 lncRNAs to be differentially expressed (fold change > 2.4) between AGA and adjacent normal tissues in a Chinese male population. Our previous study analyzed the differential expression pattern in passage-4 vs. passage-10 DP cells in a lncRNA microarray.…”
Section: Introductionmentioning
confidence: 99%